Immature gastric teratoma in an infant: A case report (Indian Journal of Case Reports, 2020)
Immature gastric teratoma is an extremely rare embryonal neoplasm. Although teratomas have been identified in most body regions, the sacrococcygeal is the most commonly involved site, followed by cervicofacial, mediastinal, gonadal, and retroperitoneal regions. The stomach is rarely involved, accounting for <1% of teratomas. Most of the cases occur in infants. The rarity of this disease in unusual sites makes the diagnosis difficult. We report an unusual case of an immature gastric teratoma in an infant who clinically presented with upper respiratory tract infection. Contrast-enhanced computed tomography abdominal was performed which revealed a large exogastric mass. Histopathological examination confirmed it to be an immature gastric teratoma. This has an excellent prognosis if treated promptly. Complete surgical excision is usually curative. Hence, awareness of this entity in unusual sites like the stomach is required to make the right diagnosis. Until date, only 35 cases of immature gastric teratomas have been reported in the published literature. We, therefore, report one such case in the stomach of a neonate.